2008
DOI: 10.1016/j.jcomdis.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on early speech, language and literacy development

Abstract: The genetic and environmental etiology of speech and broader language skills was examined in terms of their concurrent relationships in young children; their longitudinal association with reading; and the role they play in defining the 'heritable phenotype' for specific language impairment (SLI). The work was based on a large sample of 4½-year-old twins, who were assessed at home on a broad range of speech and language measures as part of the Twins Early Development Study. We found that genetic factors strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 22 publications
4
44
0
2
Order By: Relevance
“…For example, the pattern of results that emerged from cross-cultural longitudinal research on literacy is consistent with the hypothesis of greater equality leading to greater heritability (e.g. Kovas et al, 2005;Samuelsson et al, 2008;Hayiou-Thomas, 2008). The research demonstrated that heritability of reading skills varies as a function of students' age and educational set-up, including the extent to which the formal education system is able to buffer the effects of socioeconomic inequality.…”
Section: Age Cohorts Within and Across Countriessupporting
confidence: 61%
“…For example, the pattern of results that emerged from cross-cultural longitudinal research on literacy is consistent with the hypothesis of greater equality leading to greater heritability (e.g. Kovas et al, 2005;Samuelsson et al, 2008;Hayiou-Thomas, 2008). The research demonstrated that heritability of reading skills varies as a function of students' age and educational set-up, including the extent to which the formal education system is able to buffer the effects of socioeconomic inequality.…”
Section: Age Cohorts Within and Across Countriessupporting
confidence: 61%
“…However, heritability estimates for SLI have been inconsistent, suggesting that language impairments have multiple causes (Bishop, 2006). Recent research also shows that genetic factors account for individual differences in the speech of typically-developing children as well as those with SLI (Hayiou-Thomas, 2008), consistent with the view that children vary in language proficiency along multiple continuous dimensions.…”
Section: Discussionmentioning
confidence: 53%
“…Although the heritability of general language skills has been estimated to be 64% (de Zeeuw et al, 2015), other behaviour-genetic studies indicate that phonological processing skills, such as the ability to repeat nonwords, are more highly heritable and less susceptible to environmental effects than broader language abilities, such as vocabulary (Hayiou-Thomas, 2008). This leads to the prediction of a stronger association between maternal phonology and child reading/spelling than between broader (nonphonological) measures of mother’s language and child language and literacy outcomes.…”
mentioning
confidence: 99%